دور التغيير التنظيمي في تحقيق أهداف المنشئة الرياضية - والي, رفيق (My University, 2020)
الملخص : بالعربية تكمن أهمية الدراسة الحالية في إبراز دور التغيير التنظيمي في تحقيق أهداف المنشأة الرياضية من حيث تناولنا في هذه الدراسة لبعض أبعاد التغيير التنظيمي منها التطور التكنولوجي وتغيير المهام والوظائف، وقد جاءت هذه الدراسة في ثلاث جوانب الجانب المنهجي تناولنا فيه إشكالية وتساؤلات الدراسة وكذا الفرضيات والأهمية والأهداف وكذا الدراسات السابق، الجانب النظري تناولنا في فصلين التغيير التنظيمي و المنشآت الرياضية ، وأخيرا الجانب التطبيقي تناولنا في فصل منهجية الدراسة من دراسة استطلاعية والمنهج المتبع وكذا عينة البحث وتحققنا من الشروط السيكومترية لأداء الدراسة حيث بالاعتماد على مخرجات spss كانت توفرت الشروط لاستعمالها في البحث، ثم استعرضنا في الفصل الخامس نتائج الدراسة بالتحليل، وخلصنا الى النتائج التالية : يتم توصيف الوظائف بعد أحداث تغيير هيكلي بالمركب الرياضي محل الدراسة، يساعد التغيير التكنولوجي على انفتاح المركب الرياضي على المحيط الخارجي بالرغم من أن الوسائل المتوفرة بالمركب غير كافية لمواكبة هذا الانفتاح، لا تصمم برامج تدريسية جديدة عند حدوث تغيير تكنولوجي ويتم الاكتفاء بالدورات التكوينية . الكلمات المفتاحية: التغيير التنظيمي، التغيير التكنولوجي، المنشآت الرياضية. جاء هذا البحث في فصول: تناول: الفصل الأول: تناونا فيه الإطار العام للدراسة من إشكالية الدراسة وفرضياتها، وتطرقنا إلى أهمية وأهداف البحث، وكذا تحديد للمفاهيم والمصطلحات وأخيرا تناولنا الدراسات السابقة ومميزات الدراسة الحالية. الفصل الثاني: تناولنا فيه متغير التغيير التنظيمي تناولنا فيه بالترتيب، ماهية التغيير التنظيمي، الأسباب التي تستدعي التغيير، أهداف التغيير التنظيمي، أهمية التغيير التنظيمي، خصائص التغيير التنظيمي، أنواع وأنماط التغيير التنظيمي، إدارة التغيير التنظيمي. الفصل الثالث: تناولنا فيه المنشآت الرياضية،المنشآت الرياضية في العصر القديم، المنشآت الرياضية في العصر الحديث، الهيكل التنظيمي للمنشآت الرياضية، إمكانات المنشآت الرياضية، أسس ومبادئي التخطيط في المنشآت الرياضية ومزايا دراستها، التسيير المالي في المنشآت الرياضية، متغيرات البيئة العالمية وأثرها على أداء المنشآت الرياضية. الفصل الثالث: منهجية الدراسة تناولنا فيه: الدراسة الاستطلاعية ثم منهج ومتغيرات الدراسة، مجتمع وعينة الدراسة، أساليب جمع البيانات، الخصائص السيكومترية لأدوات الدراسة، تصميم الدراسة والمعالجة الإحصائية، خطوات إجراء الدراسة الميدانية. الفصل الخامس: عرض وتحليل ومناقشة النتائج، يتم فيه تحليل النتائج المحصل عليها ومناقشة الفرضيات الفصل السادس: الاستنتاجات والاقتراحات، يتم فيه عرض النتائج المتوصل اليها وتقديم بعض الاقتراحات. نتائج الدراسة:  عمال وإداريو المركب الرياضية ورتال البشير بولاية المسيلة يخضعون لدورات تدريبية إذا كان هناك تغيير تكنولوجي مثل استخدام آلات جديدة أو برامج معلوماتية جديدة وفي هذه الحالة يكون التدريب موجه لفئة العمال الذين يستخدمون هته التكنولوجيا الجديدة.  يتم توصيف الوظائف بعد أحداث تغيير هيكلي بالمركب الرياضي محل الدراسة.  يساعد التغيير التكنولوجي على انفتاح المركب الرياضي على المحيط الخارجي بالرغم من أن الوسائل المتوفرة بالمركب غير كافية لمواكبة هذا الانفتاح.  لا تصمم برامج تدريسية جديدة عند حدوث تغيير تكنولوجي ويتم الاكتفاء بالدورات التكوينية اقتراحات وتوصيات:  إجراء المزيد من الدراسات والبحوث النوعية حول التغيير التنظيمي في تحقيق أهداف المنشأت والمؤسسات.  إعادة الدراسة الحالية على قطاعات أخرى للتعرف على أوجه الشبه والاختلاف.  دراسات لدور التغيير التنظيمي في تحقيق الرضا الوظيفي.  تصورات مقترحة لتطوير المنشآت الرياضية في ظل التطور التكنولوجي. الكشاف باللغة الإنجليزية Institute: Science and Technology of Physical and Sports Activities Department: Sports Administration and Management Serial Number: Registration number: 2003307268 The student (e): Ouali Rafiq Discussion date: / Thesis Title: The role of organizational change in achieving the goals of the sports establishment, a field study of the sports complex and Al-Bashir in Al-Masila - Message language: Arabic Message type: Master University: University of Mohamed Boudiaf of M'sila Supervision of Professor: Dr. Merniz Oussama Number of pages: 103 sheets. Letter *. word * PDF. In the CD. Specialization: the management of human resources and sports facilities Summary : in Arabic The importance of the current study lies in highlighting the role of organizational change in achieving the goals of the sports establishment in terms of which we dealt with in this study some dimensions of organizational change, including technological development and changing tasks and jobs, and this study came in three aspects of the methodological aspect in which we dealt with the problems and questions of the study as well as the assumptions, importance and objectives, as well as The previous studies, the theoretical side, we dealt with in two chapters the organizational change and sports facilities, and finally the practical side we dealt in the chapter on the methodology of the study from an exploratory study and the approach followed, as well as the research sample, and we verified the psychometric conditions for the performance of the study where, depending on the outputs of spss, the conditions were met for their use in the research, then we reviewed In the fifth chapter, the results of the study analyzed, and we concluded the following results: The job description is done after the events of a structural change in the sports complex under study, the technological change helps to open the sports complex to the external environment, although the available means are not sufficient to keep pace with this openness, teaching programs are not designed New when a technological change occurs, and the training courses are sufficient. Key words: organizational change, technological change, sports facilities. This research came in chapters: The first chapter: We dealt with the general framework of the study from the problem of the study and its hypotheses, and we touched on the importance and objectives of the research, as well as defining the concepts and terminology and finally we dealt with the previous studies and the features of the current study. Chapter Two: We dealt with the organizational change variable, in which we dealt in order, what organizational change is, the reasons that require change, the objectives of organizational change, the importance of organizational change, characteristics of organizational change, types and patterns of organizational change, management of organizational change. Chapter Three: We dealt with sports facilities, sports facilities in the ancient era, sports facilities in the modern era, the organizational structure of sports facilities, the capabilities of sports facilities, foundations and principles of planning in sports facilities and the advantages of studying them, financial management in sports facilities, global environment variables and their impact on performance Sports facilities. The third chapter: The study methodology in which we dealt with: the exploratory study, then the methodology and variables of the study, the population and sample of the study, methods of data collection, the psychometric characteristics of the study tools, the study design and statistical treatment, the steps of conducting the field study. Chapter Five: Presentation, analysis and discussion of the results, in which the results obtained are analyzed and hypotheses are discussed Chapter Six: Conclusions and suggestions, in which the findings are presented and some suggestions are made. Results:  Workers and administrators of the sports complex and Rital al-Bashir in the Wilayat of M'sila undergo training courses if there is a technological change such as the use of new machines or new information programs, in which case the training is directed to the category of workers who use this new technology.  Jobs are described after the events of a structural change in the mathematical complex in question.  Technological change helps the sports complex to open up to the external environment despite the fact that the facilities available in the boat are not sufficient to keep pace with this openness.  Do not design new teaching programs when a technological change occurs, and training courses are sufficient Suggestions and recommendations: . Conducting more qualitative studies and research on organizational change in achieving the objectives of enterprises and institutions.  Repeat the current study on other sectors to identify similarities and differences.  Studies of the role of organizational change in achieving job satisfaction.  Suggested scenarios for developing sports facilities in light of technological development.
دراسة ميدانية بالمركب الرياضي ورتال البشير بالمسيلة
Keywords: التغيير التنظيمي; التغيير التكنولوجي; المنشآت الرياضية; organizational change; technological change; sports facilities